The photocatalytic process in the treatment of polluted water - Al-Nuaim, Marwah A.; Alwasiti, Asawer A.; Shnain, Zainab Y. (Chemical papers, 2023)
Wastewaters often contain toxic organic pollutants with a possible adverse effect on human health and aquatic life upon exposure. Persistent organic pollutants such as dyes and pesticides, pharmaceuticals, and other chemicals are gaining extensive attention. Water treatment utilizing photocatalysis has recently received a lot of interest. Photocatalysis is cutting-edge, alternative technology. It has various advantages, including functioning at normal temperatures and atmospheric pressure, cheap prices, no secondary waste creation, and being readily available and easily accessible. This review presented a comprehensive overview of the advances in the application of the photocatalytic process in the treatment of highly polluted industrial wastewater. The analysis of various literature revealed that TiO 2 -based photocatalysts are highly effective in degrading organic pollutants from wastewater compared to other forms of wastewater treatment technologies. The electrical structure of a semiconductor plays a vital role in the photocatalyst's mechanism. The morphology of a photocatalyst is determined by the synthesis method, chemical content, and technical characteristics. The scaled-up of the photoreactors will significantly help in curbing the effect of organic pollutants in wastewater.